Analysis of the Governance System of National Health Insurance Referral Patients at the Outpatient Polyclinic of Dian Harapanjayapura Hospital, Papua - Situmorang, Ance Melimda; Utami, Tri Niswati; Nasution, Ramadhani Syafitri (PROMOTOR, 2024)
The National Health Insurance (JKN) program, which has been running since January 1, 2014, has been widely benefited by most of the community. This program makes it easy for the public to access health services. However, the implementation of JKN for nine years often faces problems and challenges, one of which is governance. Many parties involved in this JKN program include BPJS Kesehatan as the organizer, the Ministry of Health as a regulator, Health Facilities (hospitals) as service providers and Professional Associations. This research is a qualitative research with a type of program review (governance system). The data collection process is carried out by conducting observations, interviews, analysis and documentation. Data analysis is in the form of an explanation of the situation being studied, while the presentation is in the form of a story explanation. This is in accordance with descriptive research which is the study of observations on the object of research to obtain an overview and actual circumstances. This research has been conducted at Dian Harapan Jayapura Hospital in Papua in February 2024. Based on the results of the study, it was found that inputs, processes and outputs related to the governance of National Health Insurance referral patients at the Outpatient Polyclinic of Dian Harapan Jayapura Hospital Papua were based on an assessment of human resources, facilities and infrastructure, Standard Operational Procedures, constraints and problem solving processes. The results of the study based on the influence of Human Resources show that training related to BPJS has not been carried out evenly for all personnel, including the evaluation of services has not been carried out regularly. The Assessment of Facilities and Infrastructure is considered to have been fulfilled only due to disturbances in the queue machine, the V-Claim application and Scan Finger interference. The assessment of SPO is considered to be available and understood, but there has been no routine evaluation to assess the progress of SPO implementation. The assessment of the obstacles that are often experienced is the disruption of the V-Claim Application and the queue system is still offline because the patient has not used the Mobile JKN Application so that the patient comes early in the morning to take the queue number. In terms of handling problems in stages starting from internal, if necessary, coordination between units or coordination with management with higher authority will be carried out. The conclusion in this study is that Human Resources have a great influence on services, in terms of the number that has been fulfilled, it is still necessary to evaluate the progress of services such as obstacles to delays in the doctor's practice schedule to be corrected according to the agreement so as not to affect service satisfaction. Regarding Facilities and Infrastructure, it is still considered good, it only needs to be added to facilitate online registration by increasing the benefits of the Mobile JKN Application, including the Queue Display facility at the Polyclinic. The applicable Standard Operational Procedures have been implemented, but there has not been a routine evaluation of the implementation of the SPO has been carried out appropriately or still requires additional SPOs to support services. Regarding obstacles and the solution of obstacles, it is considered good. Each officer is already independent in handling problems.